Artificial Intelligence (AI) dalam pendidikan Islam: trends, persepsi, dan potensi pelanggaran akademik di kalangan mahasiswa - Ali, Nuraliah; Hayati, Mulida; Faiza, Rohmatul; Khaerah, Alfi (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
This research explores the impact of rapid artificial intelligence (AI) growth within education, focusing on trends, perceptions of AI usage, and the potential for academic misconduct in Islamic Religious Education. The research design employs a concurrent embedded mixed-method approach, combining quantitative and qualitative data collection methods. Quantitative data is gathered through electronic surveys, while qualitative data is obtained through interviews and content analysis of documents. The findings indicate that most students have heard about AI, viewing AI-based applications as tools that can save time and effectively assist their academic assignments. However, some students express doubts regarding the effectiveness and accuracy of AI. Regarding academic integrity, the study highlights challenges associated with ensuring honesty and preventing academic misconduct. Issues such as plagiarism, cheating, and other forms of academic misconduct remain significant problems. This study emphasizes the relevance of AI in higher education, where educators need to provide guidance on the ethical use of AI within an academic context, ensuring that AI complements rather than replaces students' deep understanding, creativity, and critical thinking.